If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 10v = 42 Solving -8 + 10v = 42 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 10v = 42 + 8 Combine like terms: -8 + 8 = 0 0 + 10v = 42 + 8 10v = 42 + 8 Combine like terms: 42 + 8 = 50 10v = 50 Divide each side by '10'. v = 5 Simplifying v = 5
| 11-q=-23 | | log(6)x-log(6)(x+1)=2 | | 21n-14n=6 | | 18x-42=144 | | (3a+5y)squared= | | 1+3a=14-2a | | 11x+32=54 | | 2/7=1/3a | | 3x+1=14x+1 | | 2x^2-a=0 | | 1x=5(4x) | | v^2n^2+2vn^2-35n^2=0 | | 4x+x-4=4x+6 | | 2n-2(4n+5)=-(n-3)-8 | | 4-5(2m-3)=-11 | | 4(x+7)=8+4x | | -14+7-3b=1 | | -10(3x-7)=144 | | -10(3x-6)=144 | | Y-5=3(x-7) | | -6y-6=1-5y | | 8m+5(8m+8)=184 | | 6(x+7)=7+3(x-6)4 | | 5(m+9)=-4(10+3m) | | 3/10x-4=1/5x | | 2(x-3+2x)-x(2+6+3x)= | | Y•49/60=7/15 | | F+3pie=7pie | | 6x+4=2(x-1) | | 0.3(t-3)=-0.6+0.3t | | 5-y+5y=9 | | 8a-1(5a+1)=8-2(a-3) |